Distributed generation plants multi-agent controlling system - R. SH. Lotfullin; A. YU. Kubarev; YU. G. . Kubarev (Известия высших учебных заведений: Проблемы энергетики)
Microscopical processes of nuclear spin lattice relaxation in polydispersion ferroelectrics based on differential equation in fractional operationals are investigated. Direct bound between indexis of polydispersion and fractal dimension are established.